2012
DOI: 10.21608/ejrs.2012.50964
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of Olive Pulp in Feeding New Zealand White Doe Rabbits and Their Offspring Under the Conditions of North Sinai

Abstract: The effects of feeding four dietary treatments containing 0, 20, 25 and 30% olive pulp without nucleolus as replacement for barley grains to does and growing rabbits on nutrients digestibility and nutritive values, productive and reproductive performance, growth performance and economical efficiency were studied. The digestibility of DM, CP and CF significantly (P<0.05) decreased with increasing olive pulp level up to 30%. However, digestibility of OM was not significantly affected by olive pulp inclusion. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 6 publications
1
2
0
Order By: Relevance
“…The enhancement in carcass weight by the addition of organic acids or probiotics may be due to their role in enhancing nutrient digestibility by modifying the gut microbial content (reduction in pathogenic load) and gut morphology, which leads to increased digestion and absorption of nutrients and enhanced feed conversion ratio (Afsharmanesh et al 2010 ; Elbaz et al 2021 ). In line with our findings, Mousa and Abd El-Samee ( 2002 ) reported that carcass traits of rabbits were not affected by olive pulp inclusion in rabbits’ diets. Reports have shown that diets containing CA or probiotics achieved increased carcass weight in rabbits and poultry (Abdel-Khalek et al 2012 ; El-Sawy et al 2021 ).…”
Section: Discussionsupporting
confidence: 93%
“…The enhancement in carcass weight by the addition of organic acids or probiotics may be due to their role in enhancing nutrient digestibility by modifying the gut microbial content (reduction in pathogenic load) and gut morphology, which leads to increased digestion and absorption of nutrients and enhanced feed conversion ratio (Afsharmanesh et al 2010 ; Elbaz et al 2021 ). In line with our findings, Mousa and Abd El-Samee ( 2002 ) reported that carcass traits of rabbits were not affected by olive pulp inclusion in rabbits’ diets. Reports have shown that diets containing CA or probiotics achieved increased carcass weight in rabbits and poultry (Abdel-Khalek et al 2012 ; El-Sawy et al 2021 ).…”
Section: Discussionsupporting
confidence: 93%
“…The dietary treatments had no effect on the levels of total lipids, total protein, A, G, A/G ratio, or the liver enzymes ALT and AST. According to Mousa and Abd El-Samee (2002), the inclusion of olive pulp in growing rabbit 'diets had no significant influence on the experimental groups' serum globulin, total lipid, glucose, creatinine, AST, or ALT concentrations. The same trend was noticed by Mehrez and Mousa (2011), who found that concentrations of total protein, A, G, cholesterol, urea-N, AST and ALT did not differ significantly with olive pulp inclusion in rabbit diets at levels up to 30%.…”
Section: Blood Serum Parametersmentioning
confidence: 95%
“…All diets of trials were subjected to economic evaluation. Economical efficiency is predefined as the net revenue per unit feed cost calculated from input output analysis as described by Hassan et al (1996), El-Kerdawy (1997) and Mousa and Abd El-Samee (2002).…”
Section: Economical Efficiencymentioning
confidence: 99%